Implementing Scaffolded CPBL in Digital Marketing Education: A Study of Vocational Students in Information Technology and Culinary Programs - Slamet Kurniawan Fahrurozi; Muhammad Hassan Massaty; Safira Safira (Darul Yasin Al Sys, 2026)
Although digital marketing education has received increasing attention in vocational learning contexts, research specifically examining the role of scaffolded Cooperative Problem-Based Learning (CPBL) in enhancing students’ digital business readiness remains limited. This study aims to explore how scaffolded CPBL influences vocational students’ learning experiences, motivation, and readiness for digital business practices. A qualitative approach with a case study design was employed, involving 68 students from Diploma 3 programs in Information Technology and Culinary Arts at a polytechnic institution. Participants were selected through purposive sampling. Data were collected through reflective journals and semi-structured interviews and analyzed using thematic analysis guided by the MUSIC Model of Motivation framework. The findings indicate that scaffolded CPBL enhances students’ engagement and learning performance through small-group collaboration, facilitator support, and structured learning activities. These elements foster active participation, autonomy, and deeper understanding of digital marketing concepts. Digital business readiness also emerged as a key outcome, reflected in students’ ability to apply marketing strategies, think entrepreneurially, and collaborate in solving real-world business problems. The study concludes that scaffolded CPBL plays a crucial role in preparing vocational students for employment and entrepreneurial pathways in the digital economy. These findings contribute to constructivist learning and motivation theory and extend understanding of CPBL implementation in vocational digital marketing education. The implications of this research include practical recommendations for educators and vocational institutions to integrate problem-based and scaffolded learning approaches into digital marketing curricula and to design more industry-relevant learning experiences. The study also identifies opportunities for future research on CPBL implementation in practice-based vocational courses and longitudinal evaluation of students’ career outcomes.